DEPRESSÃO E EVENTOS ESTRESSORES EM IDOSAS QUE FREQÜENTAM GRUPOS DE CONVIVÊNCIA - Rieth, Giovani H.; Zambonato, Daiana; Stumm, Eniva M. F.; Hildebrandt, Leila M.; Kirchner, Rosane M.; Battisti, Iara D. E.; Leite, Marinês T. (Salão do Conhecimento, 2013)
Resumo